Correction: The state of the art of adeno-associated virus-based vectors in gene therapy - Nardi Nance; dos Santos Coura Renata (Virology Journal, 2010)
Abstract It has come to our attention that, on writing our manuscript (dos Santos Coura and Nardi, 2007), we unintentionally included unquoted passages from the work by Wu et al. (2006), collected during the period when we were doing extensive readings on the subject, and not adequately referenced. We regret this error and offer our sincere apologies.